Effects of different TENS electrode types in degenerative joint disease of the hands [RIZARTROZDA TENS UYGULAMALARINDA DEGISIK ELEKTRODLARIN ETKILERI] - (:unkn) unknown (My University, 1995)
Degenerative joint disease of the hand (or Risarthrosis) is seen usually after the fourth decades. The pain and the deformity of the little joints of the hand due to the disease, regress the functional status of the patient. Transcutaneous nerve stimulation (TENS), is widely used to relieve the pain and to improve the functional status in degenerative arthritis. The aim of this study is to compare the efficacy of different TENS electrode applications in the symptomatic treatment of primary osteoarthritis of the hand. Patients (36 female) were randomly assigned into two groups. TENS was applied by a glove electrode in the first group and the carbon siliconized electrode in the second group for five consecutive days. The pain and the functional status of the patients were evaluated prior to and after the treatment. As a result the efficacy of TENS application with glove electrode in relieving pain was found to be significantly (p<0.0005) superior. No significant differences were observed between the two groups in the assessment of functional status (p>0.5).
Keywords: Degenerative joint disease of the hands; Electrodes; Electrotherapy; TENS